2007
DOI: 10.1371/journal.pone.0000897
|View full text |Cite
|
Sign up to set email alerts
|

Only Half Right: Species with Female-Biased Sexual Size Dimorphism Consistently Break Rensch's Rule

Abstract: BackgroundMost animal species display Sexual Size Dimorphism (SSD): males and females consistently attain different sizes, most frequently with females being larger than males. However the selective mechanisms driving patterns of SSD remain controversial. ‘Rensch's rule’ proposes a general scaling phenomenon for all taxa, whereby SSD increases with average body size when males are larger than females, and decreases with body size when females are larger than males. Rensch's rule appears to be general in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
146
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(156 citation statements)
references
References 34 publications
(100 reference statements)
10
146
0
Order By: Relevance
“…Unlike previous studies on SSD in invertebrates these results consistently corroborated Rensch's rule [18] . Figure 1 shows the finding for Centrobolus where mean volume ratios ranged from 0.63-2.72 with the regression of log male volume on log female volume was highly significant with a positive slope less than 1; showing females get larger than males with an increase in body size [4,7,9] .…”
Section: Discussionsupporting
confidence: 86%
“…Unlike previous studies on SSD in invertebrates these results consistently corroborated Rensch's rule [18] . Figure 1 shows the finding for Centrobolus where mean volume ratios ranged from 0.63-2.72 with the regression of log male volume on log female volume was highly significant with a positive slope less than 1; showing females get larger than males with an increase in body size [4,7,9] .…”
Section: Discussionsupporting
confidence: 86%
“…1, and exceptions to this only occurred when females were the larger sex. An extensive comparison across birds found that RR is commonly broken where female-biased SSD occurs within a clade [7]. Recently, Blanckenhorn et al [31] evaluated the evidence for RR in a range of insect orders: the rule was found to apply consistently to Diptera and Heteroptera, but not to any of the other insect groups examined.…”
Section: Discussion (A) Allometry Of Sexual Size Dimorphismmentioning
confidence: 99%
“…The demonstration that females are the more variant sex (or indeed that there is no difference in degree of variation, i.e. isometry) in a range of taxa has led to the generality and utility of the rule being questioned [7,8]. As an alternative, quantitative genetic theory predicts that greater interspecific variance in size occurs in the sex that has historically been under stronger directional selection [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The latter has become to be considered the standard definition of Rensch's rule [53,54] but its interpretation is ambiguous. Although in male-biased SSD the rule is usually clearly demonstrated, in the opposite situation (female-biased SSD) the situation is far from clear [55]. This is most relevant because in a vast majority of insects and particularly in grasshoppers females are usually larger than males.…”
Section: Rensch's Rule Is Affected By Bergmann's Rule or Itsmentioning
confidence: 99%